The Strength of Cross‐Language Interdependence for Listening Comprehension Proficiency in Turkish–Dutch Emergent Bilinguals: Testing Three Hypotheses. Issue 2 (26th November 2020) - Sierens, Sven; Van Gorp, Koen; Slembrouck, Stef; Van Avermaet, Piet
Abstract: This study aimed to test three competing hypotheses concerning the strength of the cross‐language relationship in listening comprehension proficiency in emergent bilinguals: Cummins's developmental linguistic interdependence hypothesis, Proctor, August, Snow, and Barr's interdependence continuum hypothesis, and Goodrich, Lonigan, Kleuver, and Farver's language independence hypothesis. We assessed 75 Turkish–Dutch bilingual children attending Dutch‐medium schools using a two‐wave design. This involved an assessment of sentence comprehension when the children were in preschool, followed by an assessment of their discourse comprehension in 1st grade. Correlational, multiple regression, and path analyses indicated significant positive and medium‐sized L1–L2 relationships between listening comprehension proficiency at the two points in time yet not over time. These findings were consistent with the developmental linguistic interdependence hypothesis for sentence comprehension and with the developmental linguistic interdependence and the language independence hypotheses for discourse comprehension. We advocate a multidimensional explanatory framework to explore the moderating role of type of skill in determining the strength of the cross‐language relationship. Abstract :